Una nueva especie del género Xorides Latreille (Hymenoptera: Ichneumonidae) del estado de Tamaulipas, México - Ruíz Cancino, Enrique; R. Kasparyan, Dmitri (Instituto de Ecología, A.C., 2000)
Xorides madronensis sp. nov. from the Sierra Madre Oriental in the State of Tamaulipas, México, is described. This species is the second one known in the subgenus Exomus Townes et Townes. An identification key to females and males of three species of the genus Xorides discovered in México is included.